If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 26 = 2x + 4 Reorder the terms: 26 + x = 2x + 4 Reorder the terms: 26 + x = 4 + 2x Solving 26 + x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 26 + x + -2x = 4 + 2x + -2x Combine like terms: x + -2x = -1x 26 + -1x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 26 + -1x = 4 + 0 26 + -1x = 4 Add '-26' to each side of the equation. 26 + -26 + -1x = 4 + -26 Combine like terms: 26 + -26 = 0 0 + -1x = 4 + -26 -1x = 4 + -26 Combine like terms: 4 + -26 = -22 -1x = -22 Divide each side by '-1'. x = 22 Simplifying x = 22
| 2x+y=110 | | (Y-6)-(y+6)=7y | | Y=ln(e^7x) | | 4x-10=-60-10x | | 41-5x=14-8x | | x+(x*0.28)=100 | | 10+6x=-15+x | | 3x-9=x+27 | | Ln(x-3)= | | -(-1k+1)=-5(1-6k)+7k | | b+3=3 | | y-9=-17 | | 4.8x+38.3=10.9-8.9x | | 1/3x-5/6=1/9x | | sqrt(2x^2-5x-3)=x+1 | | 15x^2+3x= | | x+sqrt(25-x^2)=7 | | 5y*2y-3= | | x^2+sqrt(25-x^2)=7 | | 2(x+1)+3x+6=4 | | 15x-7=-2 | | t^2+4t+3=0 | | 28=2x+2 | | 3lnx^6-2lnx^2=14 | | 3ln(x^6)-2ln(x^2)=14 | | 3x-9x+5x-7x= | | cos^2x-sen^2x=0 | | 0.025p-2=0.15(p-5) | | 2.1d+18=216(d+8) | | z*8+(3-i)*z*4-3*i=0 | | 5v+3=7 | | 2q-4+8q=yq-8+3q |